Kelimpahan dan Keanekaragaman Kupu-kupu di Kawasan Taman Nasional Gunung Merbabu, Jawa Tengah - Sari, Dian Ratna; Hadi, Mochamad; Rahadian, Rully (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2016)
Butterflies are insects that have very important role in the ecosystem, they are as a pollinator of plants. Butterfly also can be used as a bio-indicator of environmental quality. This study aims to determine the species abundance and diversity of butterflies in the area of Merbabu Mountain National Park. This research was conducted in September and November 2016 in four habitat types, i.e., mixed forests, pine forests, mountain forests and streams. The study was conducted using a purposive sampling method. The data analysis used abundance index and diversity index. There are 454 individuals wich includes 61 species and 6 families. There are 11 dominant species of butterflies in Merbabu Mountain National Park, but only Ypthima pandocus that dominates in all the habitat that studied. Mycalesis moorei and Mycalesis sudra are dominant in all forest habitats and its not dominant in the habitat of the streams. Papilio peranthus and Parantica albata are dominant and only in mountain forest habitat. Diversity of butterflies in the area of Merbabu Mountain National Park can be categorized as moderate with the diversity index from 2,11 â€“ 3,37.Â Key word: Butterflies, diversity, abundance, Merbabu Mountain National Park